A study of mechanical peeling behavior in a junction assembled by two individual carbon nanotubes. (October 2016) - Sui, Chao; Luo, Quantian; He, Xiaodong; Tong, Liyong; Zhang, Kai; Zhang, Yingying; Zhang, Yong; Wu, Jianyang; Wang, Chao
Abstract: The mechanical characteristics of nano-scale interface between by carbon nanotubes (CNTs) play critical roles in macro-mechanical properties of CNT-based hierarchical composites. In this study, an in-situ peeling experiment for a sidewall-contacted junction assembled by two individual CNTs was achieved by using a force measurement system in the scanning electron microscope. The whole peeling mechanical behaviors were investigated by a typical peeling force-displacement curve combining with corresponding experiment video, and an interesting double peaks phenomenon about peeling force was observed. In order to further reveal this peeling process, a model of two-dimensional finite element analysis was developed, where an equivalence of rectangular sections to cylindrical sections of CNTs and a bilinear cohesive law were employed. The theoretical prediction of peeling behaviors was agreed with the experimental one. More importantly, by this model it is found that the double peaks of peeling force result from shape transition of CNTs from concave to arc, with an abruptly interface crack. This work could provide an in-depth understanding on mechanical behaviors of CNT-based hierarchical composites.